The Study of Otoacoustic Emissions and the Suppression of Otoacoustic Emissions in Subjects with Tinnitus and Normal Hearing: An Insight to Tinnitus Etiology - Serra, Lucieny; Novanta, Gabriela; Sampaio, Andre Lopes; Augusto Oliveira, Carlos; Granjeiro, Ronaldo; Braga, Silvia Cristina (International Archives of Otorhinolaryngology, 2015)
Introduction Analysis of the suppression effect is a simple method to evaluate cochlear status and central auditory mechanisms and, more specifically, the medial olivocochlear system. This structure may be involved in the generation of mechanisms that cause tinnitus and in the pathophysiology of tinnitus in patients with tinnitus and normal hearing.Objective To review the literature of the etiology of tinnitus on the lights of otoacoustic emissions in patients with normal hearing.Data Synthesis Individuals with tinnitus and normal hearing have a higher prevalence of alterations in transient-evoked otoacoustic emissions and distortion-product otoacoustic emissions than normal subjects. This fact suggests that dysfunctions of the outer hair cells (OHCs) might be important in the generation of the tinnitus; however, this feature is not always present in those who have the symptoms of tinnitus.Final Comments These findings suggest that OHC dysfunction is not necessary for tinnitus development—that is, there might be mechanisms other than OHC damage in the tinnitus development. On the other hand, OHC dysfunction alone is not sufficient to cause the symptom, because a great many individuals with OHC dysfunction did not complain about tinnitus.
Keywords: tinnitus; organ of Corti/physiology; otoacoustic emissions